The relationship between environmental cost on organisational performance and environmental management system: a structural equation modelling approach - Mohd Fuzi, Nursyazwani; Habidin, Nurul Fadly; Adam, Sabrinah; Ong, Sharon Yong Yee (Emerald Publishing, 2021)
Purpose – This study aims to examine the relationship between environmental cost (EC) on organisational performance (OPM) through an environmental management system (EMS) as the mediating variable. Design/methodology/approach – A total of 2,600 manufacturers were identified and consequently selected as the entire study population. Additionally, this study used the structural equation modelling technique to identify the mediator effects of EMS between EC and OPM. Findings – The EC and EMS relationship on OPM produced direct and indirect consequences. Hence, it is concluded that manufacturing industry in Malaysia are focused on the OPM when implementing EC and EMS. Originality/value – The model would incorporate EC and EMS implementation on OPM in the Malaysian manufacturing industry. This study could also be advantageous to the industry in improving EC, EMS and OPM.